Analgesic Efficacy of Piroxicam Compared to Paracetomol in the Treatment of Post Extraction Dental Pain - Periasamy, Yashila; Kumar, Jagdish; Ganapathy , Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
Paracetomol is an NSAID with only analgesic properties it doesn’t relieve inflammatory pain.The analgesic activity of piroxicam, a well-known NSAID has been documented in many pain states. The purpose of this study was to assess the efficacy and the rapidity of action of piroxicam in comparison with standard paracetamol following surgical extraction of teeth.The aim of the study was to compare the efficacy and rapidity of action of piroxicam and paracetamol in the treatment of post extractive dental pain The study consisted of 30 patients of both sexes and in good health. Patient seeking dental extraction were included in this study. They were specifically selected on the criteria of reporting to Saveetha dental college and hospitals for tooth extractions only. Each participant was given a brief explanation of the study, and informed consent was obtained from each participant before inclusion in the study.From the result of this study, it is clearly evident that patient who received piroxicam has less dental pain when compared with patient who received paracetamol. This will help clinicians in prescribing medication after dental extraction.